1997
DOI: 10.1111/1467-6427.00048
|View full text |Cite
|
Sign up to set email alerts
|

Brief Therapy in Adult Psychiatry – Further Outcomes

Abstract: A report of a one-year follow-up of thirty-six referrals treated with solutionfocused brief therapy by a supervised team in a mental health setting is described. A good outcome was reported for twenty-three cases (64%). These results are comparable with our previous work and with one other statistically validated outcome study on solution-focused therapy. IntroductionAs financial stringency begins to affect healthcare in all countries, there is an increasing need for outcome studies in order to guide the work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Several clinicians outside of the original group of SFBT developers have also done follow-up studies on SFBT (Lee, 1997;Macdonald, 1997;Morrison, Olivos, Dominguez, Gomez, & Lena, 1993;Schorr, 1997). In addition, Schorr used a pre-post test design using the State-Trait…”
Section: Solution-focused Brief Therapy Researchmentioning
confidence: 99%
“…Several clinicians outside of the original group of SFBT developers have also done follow-up studies on SFBT (Lee, 1997;Macdonald, 1997;Morrison, Olivos, Dominguez, Gomez, & Lena, 1993;Schorr, 1997). In addition, Schorr used a pre-post test design using the State-Trait…”
Section: Solution-focused Brief Therapy Researchmentioning
confidence: 99%
“…Vertinant rigidiškumo įtaką konsultacijų dažnu-mui, galima prielaida, kad labiau rigidiškiems paaugliams dėl jiems būdingo mažesnio socialumo ir bendravimo sunkumų (23) gali būti sunkiau suprasti būtiny-bę keisti savo elgseną, todėl, siekiant teigiamų pokyčių, šiems paaugliams reikia daugiau laiko ir pagalbos. Tai, kad paaugliams, kurie konsultacijų metu sprendžia-mą problemą vertino kaip lengvesnę, reikėjo mažiau konsultacijų sprendimams rasti, atitinka kitų autorių pastebėjimus, kad geresnių konsultacijos rezultatų pasiekiama, kai sprendžiamos problemos lengvesnės (24).…”
Section: Rezultatų Aptarimasunclassified
“…Several clinician‐researchers outside the Milwaukee group have also conducted followup studies of SFBT (Lee, 1997; Macdonald, 1997; Morrison, Olivos, Dominguez, et al, 1993; Schorr, 1997). For the most part, these studies also used subjective outcome measures and found similar but somewhat smaller success rates.…”
Section: Early Followup Studiesmentioning
confidence: 99%